Use factoring and the zero-product property to solve the following problems:

z(z - 1)(z + 3) = 0

x^2 - x - 10 = 2

4a^ - 11a + 6 = 0

9r^r - 30r + 21 = -4

Please show work. Thank you so much!

2 answers

the first one is already factored, so how come you are stuck on it ?

2nd:
get the equation = 0
then it factors quite easily

4a^2 - 11a + 6 = 0 and 9r^r - 30r + 21 = -4

have you not been taught some kind of a method to factor these kind of trinomials?
A common method these days is "decomposition"
Thanks. :) I think I got it now. You rock.